From Green HRM to Environmental Performance: An AMO-Based Behavioral Framework for the Pharmaceutical Industry (Journal of Informatics Education and Research, 2025)
Sustenance of environmental degradation and the growing regulatory pressure have urged organizations, especially those in the pharmaceutical industry to entrench sustainability in their fundamental operating systems as well as in their human resource process. The present paper constructs an elaborate conceptual framework underpinning the notion of how Green Human Resource Management (GHRM) practices can improve the environmental performance by pro-environmental behaviors of employees (PEB). The model is based on the Ability-Motivation-Opportunity (AMO) framework whereby the model contends that green abilities (training and recruitment), green motivation (rewards, appraisal, engagement) and green opportunities (participation, autonomy, flexible structures) will all combine to create a workplace climate that fosters both voluntary and required environmental behaviors. The paper has synthesized the empirical evidence on how it mediates the environment due to both GHRM systems and the environment through an integrative review of both global and Indian studies (2015-2025). The pharmaceutical manufacturing concerns mentioned in the review, such as waste handling, effluent management, and the compliance requirements are also sector-specific, which makes employee-level involvement essential. The paper provides a theoretical contribution to the field by deriving the AMO model into a multi-level, behavior-based green HRM model and gives a straightforward agenda of future empirical studies based on propositions on the topic, which can be tested. There are also managerial recommendations and sector oriented implications provided to enhance sustainability efforts in the pharmaceutical industry.